PERENCANAAN MANAJEMEN SUMBER DAYA MANUSIA - Samsuni Samsuni (ADISAM PUBLISHER, 2024)
Human resource planning is part of the management process flow in determining the movement of the company's human resources, from the current position to the desired position in the future. Thus, the success of human resource planning will be determined by the accuracy of selecting strategies in designing the empowerment of the company's human resources and predicting future needs in accordance with the dynamics of the company's business growth and development. Viewed from a management process perspective, human resource planning is not just related to the staffing function. But more than that, human resource planning includes various functional operations in implementing human resource management which are aligned with the implementation of the company's strategic management.